2024
DOI: 10.1007/s10072-024-07561-1
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-tactile stimulation of the neck reduces pain in people with cervical dystonia: a proof-of-concept study

Jiapeng Xu,
Matteo Costanzo,
Laura Avanzino
et al.

Abstract: Background Pain is a common non-motor symptom in patients with cervical dystonia (CD), severely impacting their quality of life. The pathophysiology of CD is incompletely understood but it involves altered processing of proprioceptive and pain signals. Objectives The purpose of this proof-of-concept study was to determine if vibro-tactile stimulation (VTS)—a non-invasive form of neuromodulation targeting the somatosensory system—can modulate neck pain in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This VTS-induced electrocortical effect is similar in nature to what is observable in people with cervical dystonia who apply sensory tricks ( 23 ) suggesting that effectiveness of VTS and sensory tricks may share a similar neural mechanism. With respect to other forms of focal dystonia, a case study ( 24 ) reported that VTS applied to trapezius muscles normalized the head posture of a patient with torticollis and neck muscle VTS may reduce pain associated with cervical dystonia ( 25 ). In summary, previous research established proof-of-concept of the short-term effectiveness of VTS in treating the symptoms of focal dystonia and provided insights into the underlying neural mechanism behind its effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This VTS-induced electrocortical effect is similar in nature to what is observable in people with cervical dystonia who apply sensory tricks ( 23 ) suggesting that effectiveness of VTS and sensory tricks may share a similar neural mechanism. With respect to other forms of focal dystonia, a case study ( 24 ) reported that VTS applied to trapezius muscles normalized the head posture of a patient with torticollis and neck muscle VTS may reduce pain associated with cervical dystonia ( 25 ). In summary, previous research established proof-of-concept of the short-term effectiveness of VTS in treating the symptoms of focal dystonia and provided insights into the underlying neural mechanism behind its effectiveness.…”
Section: Introductionmentioning
confidence: 99%